Bipatride for Indonesian Diaspora - Reumi, Tom Alfa S. (Papua Law Journal, 2017)
This study aims to determine the status of dual citizenship law (bipatride) for overseas Indonesian overseas (Diaspora). This research is prescriptive legal research with normative juridical approach method in the form of research on the principle of citizenship law with data collection technique through literature study in the form of primary, secondary and tertiary law material with qualitative legal material analysis. The results of the study show that Law No. 12 of 2006 on Citizenship recognizes only limited dual citizenship that the status of the Diaspora citizenship is limited. However, there is a need for further regulation regarding the limitation of the use of this limited dual citizenship because in the Act does not regulate the consequences of circumstances that allow a person to not choose one of his nationalities in the event that the person has limited dual citizenship status.